Association of Ureaplasma diversum with reproductive disease in cattle. Issue 5 (3rd September 2019) - Díaz, JM; Prieto, A; López, G; Díaz, P; López, C; Quintela, LÁ; Morrondo, P; Fernández, G
ABSTRACT: Aims: To examine the association between the detection of Ureaplasma diversum in vaginal swabs from dairy cows in north western Spain with the diagnosis of granular vulvovaginitis (GVV) and reproductive performance, and the association with subclinical endometritis (SE) in slaughterhouse material. The presence of this microorganism in cases of abortion was also investigated. Methods: From 106 dairy farms in the province of Lugo, 40 herds were randomly selected. Vaginal swabs were obtained from 10 randomly selected cows per farm, then pooled for analysis to detect the presence of U. diversum by quantitative real-time PCR (qPCR). In five of these herds samples from the 10 animals were individually tested for U. diversum, and the presence of GVV lesions and their reproductive efficiency (number of inseminations to achieve pregnancy over two subsequent pregnancies) were determined. Vaginal swabs from uteri of cattle obtained at a slaughterhouse (n = 100) were tested for U. diversum and the presence of SE, defined as >5% polymorphonuclear cells in cytobrush smears, was determined. Sixteen farms with abortion problems submitted samples for culture and PCR testing including for U. diversum . Results: Of the 40 herds, 39 (98%) tested positive for U. diversum . On the five farms, 25/50 (50%) cows tested positive for U. diversum, and more cows with GGV-lesions (16/25; 64%) tested positive than cows without lesions (9/25; 36%) (p = 0.047). There were more cows with poor reproductive efficacy that tested positive (8/11; 57%) than tested negative (3/17; 18%) for U. diversum (p = 0.029). Of the 100 uteri, five tested positive for U. diversum and there were more uteri with SE that tested positive (3/19; 16%) than uteri without SE (2/81; 2%) (p = 0.036). U. diversum was also diagnosed in 4/16 farms with abortion problems and liver appeared to be the best tissue for detecting U. diversum DNA in the fetuses analysed. Conclusions and Clinical Relevance: Infection with U. diversum was present in most of herds investigated and it was statistically associated with GVV, SE and poor reproductive performance. It was also detected in abortions and the liver may also be an additional tissue to be considered in the diagnosis of U. diversum abortion by PCR. The possible association with different diseases in the same area suggests that different presentations should be considered when studying the implications of U. diversum on the reproductive diseases of cattle.